Reproductive potential of Spodoptera eridania (Stoll) (Lepidoptera: Noctuidae) in the laboratory: effect of multiple couples and the size - Specht,A. (2016)
Abstract This study aimed to evaluate the effect of keeping three couples in the same cage, and the size of adults emerged from small, medium-sized and large pupae (278.67 mg; 333.20 mg and 381.58 mg, respectively), on the reproductive potential of S. eridania (Stoll, 1782) adults, under controlled conditions (25 ± 1 °C, 70% RH and 14 hour photophase). We evaluated the survival, number of copulations, fecundity and fertility of the adult females. The survival of females from these different pupal sizes did not differ statistically, but the survival of males from large pupae was statistically shorter than from small pupae. Fecundity differed significantly and correlated positively with size. The number of effective copulations (espematophores) and fertility did not vary significantly with pupal size. Our results emphasize the importance of indicating the number of copulations and the size of the insects when reproductive parameters are compared.